Assessment of Noise Exposure Indices at Kanchijhuli and Townhall Moor in Mymensingh City (Journal of Environmental Science and Natural Resources, 2022)
Mymensingh, one of Bangladesh's most densely populated and urbanized cities, could not avoid a noise-related problem that has now turned out into a severe environmental issue. It is indispensable to assess the current noise propagation scenario and its repercussions for urban planners to manage the noise problem. This research endeavours to construct noise pollution indices viz. noise levels (L10, L50, L90), noise climate (NC), equivalent continuous noise level (Leq), noise pollution level (Lnp), and noise exposure index (NEI) were computed for two important particular locations, namely Kanchijhuli and Townhall moor. It was also observed that most of the time, the noise level exceeded 80 dB, which is beyond the recommended level of silent zone, commercial zone and traffic zone according to the DoE (1997). The indices indicated that the noise level of the study area surpassed the normal noise level in all indices. NC, Leq and Lnp were estimated to have a maximum value of 17.32 dB, 94.29 dB and 110.30 dB, respectively, while the minimum value of the study area were 10.71 dB, 82.07 dB and 95.5 dB, respectively. Therefore, it can be stated from the assessment that both Kanchijhuli and Townhall moor are under alarming noise pollution conditions. This research may aid in taking necessary measures to cut off the noise propagation and subsequent noise pollution control for the urban planners and related authorities.Environ. Sci. & Natural Resources, 13(1&2): 19-24, 2020